ANALISIS EFISIENSI TEKNIS ALOKATIF DAN EKONOMI PADA USAHATANI SEMANGKA DI DESA MOJOARI KECAMATAN PUGER KABUPATEN JEMBER - Rahmah Raisha Fadliyah; Evita Soliha Hani (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2019)
ABSTRACT Common problems that often occur and impacted the local farmers in Desa Mojosari are the unpredictable weather condition and all-year farming without switching the variety of the plants grown. The fluctuation in productivity value also correlates with the use of many production factors and the efficiency in input usage. Another known problems are the acceptance of watermelon farming that is often less considered and that it still hasn’t reach the highest value of profit. The goal of this research is to understand the many factors that impacted watermelon farming, it’s technical efficiency, it’s allocative efficiency and it’s economical efficiency. The analysis tool used in this research is cobb douglas with Scohastic frontier analysis approach. Sampling method used in this research is proportionate stratified random sampling in which 64 farmer samples are acquired. This research resulted in (1) farming denominator of the watermelon that has definitive impacts in partial are the land area’s size variable (X1), seeds (X2) and organic fertilizer (X6) while drugs (X3), chemical fertilizer (X4) dan manpower (X5) do not leave an actual impact. (2) Watermelon farming does not reach an efficient production number as it only has a value of 69% in which can still be grown to another 31%. (3) Watermelon farming is allocatively inefficient as it only has an NPM value of (< 1) (4) Watermelon farming has an economical value efficiency of 2,84>1, meaning that the watermelon farming is not economically efficient.